A3.10 Characterisation of CD4+ T cell response and effects of regulatory T cells in pristane induced lupus (PIL). (31st January 2014) - Leiss, H; Schwarzecker, B; Gessl, I; Niederreiter, B; Smolen, JS; Stummvoll, GH
Abstract : Introduction: CD4+ T cells and the Th1 subset in particular play a pivotal role in SLE. Regulatory T cells (Treg) are essential for maintaining peripheral tolerance, but their number and function in SLE is decreased. We herein characterise CD4+ T cell and Treg homeostasis as well as the effects of intravenous administration of exogenous Treg on disease severity in a model of induced systemic lupus. Methods: Mice were injected ip. with 0.5ml of pristane or PBS as control and killed after 8 months. Cell suspensions with CD4+ FoxP3+ cells (iTreg) were injected intravenously: when PIL was induced (5 x 10e6, iTreg-boost) or every 4 weeks (1 x 10e6, iTreg-repeated). Animals were monitored for clinical signs of arthritis and in order to analyse and compare disease severity, histological features of arthritis and pneumonitis were quantified by an image analysis system (Osteomeasure®). Lymphocytes were isolated from granulomas (ectopic lymphoid tissue within the peritoneum), lymphnodes (LN) and spleens and were analysed separately for each mouse by FACS. Results: Clinically, PIL presented involvement of inner organs; most frequently affected were the lungs (100% pneumonitis) and the joints, whereas 52% out of the PIL group and 36% of the Treg-treated groups developed clinical arthritis. Monthly iTreg significantly decreased clinical signs of arthritis and histological lung and joint parameters. Out of 6 mice treated, 4 (66%) did not show any signs of arthritis at all. One-shot iTreg did not prevent joint manifestations or pneumonitis, but seemed to have a retarding effect indicated by a delayed onset of clinical symptoms and by a significantly decreased erosive area. Intraperitoneal granuloma typical for PIL appeared to be the hotspots of inflammation showing a significantly elevated Teff/Treg ratio of 1.3. Upon re-stimulation, CD4+ cells showed a pronounced Th1 response (27% IFNγ producers) compared to LN and spleens from both PIL and HC (with Th1 percentages ranging from 9-16%), but also frequencies of Th2 and Th17 cells were elevated in PIL, again with the highest yield in granuloma. iTreg reduced the Teff/Treg ratio in PIL granuloma to 0.7. Conclusion: Repeated injections of exogenously induced Tregs reduce the Teff /Treg ratio as well as the severity of pneumonitis and arthritis. A single boost of Tregs even when applied before the clinical onset cannot decrease all parameters, but appears to retard onset of symptoms and progression. Thus, iTreg have significant effects on lupus symptoms when applied repeatedly, which may have consequence for future therapeutic considerations.